Investigation of Coronary Artery Anomalies and Myocardial Ischemia: A Case Study at the University Clinical Center of Kosovo - Rilind Sylaj; Jeton Shatri; Premtim Rashiti; Afrim Shabani; Aurora Bakalli; Shpend Elezi; Faik Asllani (International Journal of Biomedicine)
Background: This research examines how coronary artery anomalies (CAAs) relate to myocardial ischemia based on a case study from the University Clinical Center of Kosovo (UCCK). We aim to improve clinical knowledge about CAAs, measure CAA occurrence within Kosovo's population, and identify risk factors leading to myocardial ischemia. Methods and Results: Data analysis of 44 patients aged 55 and older who received CAA diagnoses followed a retrospective cohort study design. The research examined four key aspects: patient demographic characteristics, clinical diagnoses, vessel disease classification, and electrocardiographic detection of myocardial ischemia. The sample analysis showed that males comprised 68.2% of participants and that the largest percentage of subjects fell within the 55-59 age group (31.8%). ST-elevation myocardial infarction (STEMI) was the most prevalent diagnosis at 45.5%, while half the patients presented multivessel disease. The research identified important connections between patient gender and smoking habits, on the one hand, and the incidence of STEMI diagnoses on the other. The analysis found no statistically significant connection between coronary artery anomalies and ischemic changes on electrocardiograms. Conclusion: The research advises implementing routine CAA screening in at-risk demographics. It suggests a multidisciplinary method for better diagnostic precision while recommending extensive multi-center research to confirm findings and investigate long-term effects.